Pandangan Tokoh Organisasi Keislaman Terhadap Fatwa MUI Tentang Shalat Berjamaan Masa Pandemi Covid-19 - Nurul Hijrah; Syaiful Aziz (Universitas Islam Negeri Raden Fatah Palembang, 2023)
MUI Fatwa No 14 of 2020 states that pilgrims must wear masks covering their mouths and noses in order to avoid air contact between one congregation and another congregation. This has elicited a different reaction from the people of South Sumatra, especially Palembang, because the procedures for congregational prayers that have been carried out by Muslims so far refer to the Shari'a that has been established by Islam, namely in accordance with the procedures taught by the Prophet Muhammad. This research is a type of empirical normative research. The type of research method used by the author is the combination of the two elements, namely examining through a product analysis approach that tends to be perspective. The type of data used in this research is qualitative, while the data source uses two sources, namely primary data sources and secondary data sources. The results of the study concluded that the South Sumatran Indonesian Islamic Da'wah Council expressed an opinion that maintaining distance in congregational prayers is haram because it has exceeded the limit, unless it is in accordance with the Shari'a. The South Sumatra Indonesian Islamic Propagation Council and the Muhamadiyah Regional Leaders implemented MUI Fatwa No. 14 of 2020 concerning Organizing Worship during the Covid-19 Outbreak.